2024
DOI: 10.3389/fbioe.2024.1343294
|View full text |Cite
|
Sign up to set email alerts
|

Performance of 3D printed porous polyetheretherketone composite scaffolds combined with nano-hydroxyapatite/carbon fiber in bone tissue engineering: a biological evaluation

Lian Mi,
Feng Li,
Dian Xu
et al.

Abstract: Polyetheretherketone (PEEK) has been one of the most promising materials in bone tissue engineering in recent years, with characteristics such as biosafety, corrosion resistance, and wear resistance. However, the weak bioactivity of PEEK leads to its poor integration with bone tissues, restricting its application in biomedical fields. This research effectively fabricated composite porous scaffolds using a combination of PEEK, nano-hydroxyapatite (nHA), and carbon fiber (CF) by the process of fused deposition m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The main limitation of these carbon nanomaterials is their size, which is generally less than 200 nm, with the risk of being eliminated by the human immune system or the target organ [18][19][20]. We and others have shown that ACs, under the form of carbon fibers, are interesting materials for bone reconstruction [21][22][23][24][25][26]. In pilot studies performed in a rat model of large bone cortical defects, we have shown that activated carbon fiber cloth is highly biocompatible and fully osteointegrated after 6 months post-surgery [27].…”
Section: Introductionmentioning
confidence: 99%
“…The main limitation of these carbon nanomaterials is their size, which is generally less than 200 nm, with the risk of being eliminated by the human immune system or the target organ [18][19][20]. We and others have shown that ACs, under the form of carbon fibers, are interesting materials for bone reconstruction [21][22][23][24][25][26]. In pilot studies performed in a rat model of large bone cortical defects, we have shown that activated carbon fiber cloth is highly biocompatible and fully osteointegrated after 6 months post-surgery [27].…”
Section: Introductionmentioning
confidence: 99%